A Method for Visualizing Independent Spatio-Temporal Patterns of Brain Activity. (5th July 2009) - Krusienski Krusienski, Dean J. Dean J.
Abstract : Evoked and coordinated brain signals often exhibit distinct, individualized spatial and temporal characteristics, such as amplitude and phase couplings across and within spatial channels. In the study of these brain potentials, it is important to characterize both the spatial and temporal morphologies of the responses for a better understanding of both the physiology and function of the brain. This paper presents a method for visualizing the characteristic spatio-temporal brain activity associated with two distinct conditions. This method, called Independent Spatio-Temporal Patterns (ISTPs), extends Common Spatial Patterns (CSPs) for spatio-temporal pattern visualization by adding temporal features. Independent component analysis (ICA) is then applied to extract independent spatio-temporal patterns corresponding to each condition. The results indicate that the inclusion of temporal features can provide useful insight regarding the spatio-temporal characteristics of sensorimotor rhythms.